Shedding of Hepatitis C Virus Into the Rectum of HIV-infected Men Who Have Sex With Men. (24th December 2016) - Foster, Andrew L; Gaisa, Michael M; Hijdra, Rosanne M; Turner, Samuel S; Morey, Tristan J; Jacobson, Karen B; Fierer, Daniel S
Abstract : HCV was shed in non-blood rectal fluid of 47% of HIV-infected MSM, with a range of 2.6 to 5.5 log10 IU/mL. The presence and magnitude of rectal HCV shedding was strongly associated with magnitude of blood VL. Abstract: Background: For over a decade we have known of an epidemic of sexually transmitted hepatitis C virus (HCV) infection among human immunodeficiency virus (HIV)-infected men who have sex with men (MSM), but there still remains significant controversy over which bodily fluid(s) are responsible for HCV transmission in these men. Methods: We enrolled HIV-infected MSM with recent and chronic HCV infection and quantified HCV from rectal fluid obtained by blind swab. We compared the rectal HCV viral load (VL) with paired blood HCV VL. Results: We found rectal HCV shedding in 20 (47%) of 43 men, only one (2%) of whom had visible bleeding. Detection of rectal HCV shedding was associated with blood VL > 5 log10 IU/mL (p = .01), and 85% with blood VL > 5 log10 IU/mL had rectal shedding. The HCV VL of the rectal fluid ranged from 2.6 to 5.5 log10 IU/mL. Based on the median rectal fluid VL, the surface of an average human penis would be exposed to at least 2, 300 IU of HCV for the duration of anal intercourse. Conclusion: This study provides the first direct evidence to our knowledge that a sufficient quantity of HCV is shed into the rectum in HIV-infected men with HCV infection to directly infect an inserted penis or be passed indirectly through fomite-like transmission to the rectum of sex partner. We must develop an appropriate public health campaign to educate MSM about these routes of HCV infection to reverse the HCV epidemic among HIV-infected MSM.